Du concept d’« innovation sociale » - Prades, Jacques (Revue internationale de l'économie sociale : recma, 2015)
Un article de la revue Revue internationale de l'économie sociale, diffusée par la plateforme Érudit.
Keywords: Coopératives; Définition; Europe; Histoire; Innovation technologique; Économie

‘Shaken, but not stirred’: Sixty years of defining social innovation - Edwards-Schachter, Mónica; Wallace, Matthew (Technological Forecasting and Social Change, 2017)
This paper examines the evolution in the conceptualization of Social Innovation (SI) with a view to elucidating the multiplication of uses of the term over the last half century. We performed a comprehensive and systematic literature review extracting 252 definitions of SI through a search of 2,339 documents comprising academic papers, books and book chapters, together research and policy reports. To guide the inductive analysis of pluri-vocal discourses we assume innovation to be a learning-based process involving actors’ interactions and social practices. We apply mixed qualitative methodologies, combining content analysis based on an interpretivist ontology with cognitive mapping techniques. Our findings show that SI was introduced as an analytical concept by incipient academic communities and has spread in the last decades as a normative concept fuelled by development and innovation policies. SI is defined by a set of common core elements underpinning three different and interrelated discursive ‘areas’: processes of social change, sustainable development and the services sector. We point to some policy implications and a number of promising avenues for research towards the advancement of a broader socio-technical theory of innovation.
Keywords: Histoire

Prefigurative politics and social change: a typology drawing on transition studies - Törnberg, Anton (Distinktion, 2021)
Recent years have seen a surge of interest in prefigurative politics, which refers to the political strategies that model a future society on a micro level and aim to instantiate radical social change in and through practice. While most previous studies have focused on defining the concept and categorizing various types of prefiguration, this paper contributes by investigating under what circumstances prefiguration leads to revolutionary social change. The paper takes an original approach to these issues by turning to transition studies and the socio-technical change literature. This field focuses on the technical equivalence of prefiguration: namely, the relationship between small-scale niche innovations and large-scale technological transitions. Through theoretical discussions and empirical illustrations, this paper presents a typology of five transition pathways through which prefigurative strategies may result in a range of social change outcomes from reformative to revolutionary transformation.
Keywords: Changement social; Histoire; Innovation technologique; Libre accès; Mouvement social; Politiques; Science politique; Technologie; Transition

Theories of Social Innovation - Logue, Danielle (Edward Elgar, 2019)
As we grapple with how to respond to some of the world’s most pressing problems, such as inequality, poverty and climate change, there is growing global interest in ‘social innovation’ as a potential solution. But what exactly is ‘social innovation’? This book describes three ways to theorise social innovation when seeking to manage and organize for both social and economic progress.
Keywords: Australie; Histoire; Innovation sociale; Théorie Néo-Institutionnelle

Social innovation: how societies find the power to change - Mulgan, Geoff (Policy Press, 2019)
The 21st century has brought a cornucopia of new knowledge and technologies. But there has been little progress in our ability to solve social problems using social innovation – the deliberate invention of new solutions to meet social needs - across the globe. Geoff Mulgan is a pioneer in the global field of social innovation. Building on his experience advising international governments, businesses and foundations, he explains how it provides answers to today’s global social, economic and sustainability issues. He argues for matching R&D in technology and science with a socially focused R&D and harnessing creative imagination on a larger scale than ever before. Weaving together history, ideas, policy and practice, he shows how social innovation is now coming of age, offering a comprehensive view of what can be done to solve the global social challenges we face.
Keywords: Définition; Histoire; Innovation sociale; Politiques; Réservé UdeM; Technologie

À quoi sert l'innovation sociale - Maison de l'innovation sociale (2021)
L’histoire a vu son lot d’innovations technologiques et scientifiques dans toutes les époques et sphères de la société : dans les sciences, le transport, les infrastructures, la technologie, les communications et d’autres encore.
Keywords: Communauté d'innovation; Histoire; Innovation sociale; Invention; Libre accès; Montréal; Québec

Le temps créateur : innovation technique et discontinuité sociale - Gras, Alain (L'Homme et la société, 1985)
Tant que l'on ne considère pas dès l'abord, la durée comme constitutant interne de "l'objet sociologique", toute réflexion sur cet objet-phénomène est impossible. La temporalité incluse dans notre perception est une "réalité" de sens commun qui permet à l'imaginaire social de fonctionner comme générateur d'images". Le progrès technique est considéré comme une suite de possibles, de hasards associés qui créent la condition de l'existence d'un objet technique. L'innovation technologique n'est cependant facteur de changement que si une création socio-culturelle se produit autour d'elle.
Keywords: Histoire; Innovation technique; Libre accès; Sociologie; Transformations

À quoi sert l'innovation sociale - Maison de l'innovation sociale
L’histoire a vu son lot d’innovations technologiques et scientifiques dans toutes les époques et sphères de la société : dans les sciences, le transport, les infrastructures, la technologie, les communications et d’autres encore.
Keywords: Communauté d'innovation; Histoire; Innovation sociale; Invention; Libre accès; Montréal; Québec

Le temps créateur : innovation technique et discontinuité sociale - Gras, Alain (L'Homme et la société, 1985)
Tant que l'on ne considère pas dès l'abord, la durée comme constitutant interne de "l'objet sociologique", toute réflexion sur cet objet-phénomène est impossible. La temporalité incluse dans notre perception est une "réalité" de sens commun qui permet à l'imaginaire social de fonctionner comme générateur d'images". Le progrès technique est considéré comme une suite de possibles, de hasards associés qui créent la condition de l'existence d'un objet technique. L'innovation technologique n'est cependant facteur de changement que si une création socio-culturelle se produit autour d'elle.
Keywords: Histoire; Innovation technique; Libre accès; Sociologie; Transformations

Prefigurative politics and social change: a typology drawing on transition studies - Törnberg, Anton (Distinktion, 2021)
Recent years have seen a surge of interest in prefigurative politics, which refers to the political strategies that model a future society on a micro level and aim to instantiate radical social change in and through practice. While most previous studies have focused on defining the concept and categorizing various types of prefiguration, this paper contributes by investigating under what circumstances prefiguration leads to revolutionary social change. The paper takes an original approach to these issues by turning to transition studies and the socio-technical change literature. This field focuses on the technical equivalence of prefiguration: namely, the relationship between small-scale niche innovations and large-scale technological transitions. Through theoretical discussions and empirical illustrations, this paper presents a typology of five transition pathways through which prefigurative strategies may result in a range of social change outcomes from reformative to revolutionary transformation.
Keywords: Changement social; Histoire; Innovation technologique; Libre accès; Mouvement social; Politiques; Science politique; Technologie; Transition

Social innovation: how societies find the power to change - Mulgan, Geoff (Policy Press, 2019)
The 21st century has brought a cornucopia of new knowledge and technologies. But there has been little progress in our ability to solve social problems using social innovation – the deliberate invention of new solutions to meet social needs - across the globe. Geoff Mulgan is a pioneer in the global field of social innovation. Building on his experience advising international governments, businesses and foundations, he explains how it provides answers to today’s global social, economic and sustainability issues. He argues for matching R&D in technology and science with a socially focused R&D and harnessing creative imagination on a larger scale than ever before. Weaving together history, ideas, policy and practice, he shows how social innovation is now coming of age, offering a comprehensive view of what can be done to solve the global social challenges we face.
Keywords: Définition; Histoire; Innovation sociale; Politiques; Réservé UdeM; Technologie

Theories of Social Innovation - Logue, Danielle (Edward Elgar, 2019)
As we grapple with how to respond to some of the world’s most pressing problems, such as inequality, poverty and climate change, there is growing global interest in ‘social innovation’ as a potential solution. But what exactly is ‘social innovation’? This book describes three ways to theorise social innovation when seeking to manage and organize for both social and economic progress.
Keywords: Australie; Histoire; Innovation sociale; Théorie Néo-Institutionnelle